A method for preparing calcium carbonate by using magnesium slag circulating ammonium leaching and calcium carbonate

CN122977421APending Publication Date: 2026-10-27YULIN UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611412053.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种利用镁渣循环铵浸制备碳酸钙的方法及碳酸钙,以解决现有一次铵浸工艺中钙提取率低、杂质离子共沉淀导致产品纯度不高、以及碳化过程中镁离子共沉淀影响产品纯度的技术问题

Benefits of technology

本发明公开的一种利用镁渣循环铵浸制备碳酸钙的方法,在钙提取环节,针对镁渣中部分钙被硅酸盐包裹或以稳定物相存在、一次浸出难以完全提取的问题,本发明在一次铵浸之后,对一次浸出渣进行至少一次循环铵浸反应,使残留的钙进一步溶解,并将一次浸出液与所有循环浸出液合并,从而显著提高了镁渣中钙的总浸出率。在杂质去除环节,针对一次铵浸所得浸出液中残留的Al3+、Fe3+等杂质离子在后续碳化过程中会共沉淀进入产品、严重影响产品纯度的缺陷,本发明在碳化反应之前引入了净化处理步骤,先将混合浸出液的pH值调节至10~11,为杂质沉淀创造碱性条件,再加入碱性溶液使Al3+和Fe3+分别以氢氧化物沉淀形式析出,通过固液分离预先将杂质从体系中去除,从根本上阻断了杂质进入最终产品的路径。实施例1的产品MgO质量分数仅0.028%,远低于对比例1的0.058%,充分证明了净化处理对提升产品纯度的关键作用在碳化反应环节,通过向净化液中通入二氧化碳进行碳化反应生成碳酸钙,实现从工业固废镁渣到高纯度碳酸钙产品的完整转化,工艺条件温和,无需高温高压设备,兼具固废资源化利用与高值化产品制备的双重效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977421A_ABST
    Figure CN122977421A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing calcium carbonate by using magnesium slag cyclic ammonium leaching and calcium carbonate, and belongs to the technical field of industrial solid waste resource utilization. The method comprises the following steps: subjecting magnesium slag to digestion reaction; subjecting the material after digestion to ammonium leaching, and performing solid-liquid separation to obtain primary leaching liquor and leaching residue; subjecting the leaching residue to at least one cycle of ammonium leaching, and combining all leaching liquors to obtain mixed leaching liquor; adding ammonia water into the mixed leaching liquor to adjust pH, and then adding sodium hydroxide solution to perform purification treatment, and performing solid-liquid separation to obtain purified liquor; and introducing carbon dioxide into the purified liquor to perform carbonization reaction, so as to generate calcium carbonate. The application solves the problem of low calcium extraction rate by using the cyclic ammonium leaching, avoids the co-precipitation of impurity ions by using the purification treatment of the leaching liquor, avoids the co-precipitation of magnesium ions by controlling the carbonization process, significantly improves the product purity and yield, and realizes the high-value utilization of the magnesium slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial solid waste resource utilization technology, specifically relating to a method for preparing calcium carbonate using magnesium slag recycling ammonium leaching and the calcium carbonate itself. Background Technology

[0002] In the production of metallic magnesium, the Pidgeon process generates millions of tons of magnesium reduction slag (magnesium slag) annually, with a total stockpiled volume reaching tens of millions of tons over the years. Magnesium slag is rich in calcium (CaO mass fraction 45%~60%), possessing high resource utilization value. Utilizing magnesium slag to prepare light calcium carbonate is an effective way to utilize and transform magnesium slag into high-value resources. Currently, the main methods for extracting calcium from magnesium slag to prepare light calcium carbonate are acid leaching and ammonium leaching. Although acid leaching has high leaching efficiency, it has poor selectivity, often leaching impurities such as magnesium and iron along with the slag, requiring subsequent treatment of waste acid, resulting in high costs and significant pollution. Ammonium leaching (NH4Cl) selectively leaches calcium from magnesium slag, offering advantages such as good selectivity and a mild process, and has become the mainstream technology for extracting calcium from magnesium slag to prepare calcium carbonate.

[0003] Existing single-stage ammonium leaching-carbonization processes can selectively extract calcium from magnesium slag. However, due to the complex formation of calcium in magnesium slag—some calcium is encapsulated by silicates, while some exists in a more stable phase—a single leaching process is insufficient to completely extract calcium, resulting in a low calcium recovery rate. Simultaneously, residual Al in the leachate... 3+ Fe 3+ Impurity ions can co-precipitate into the product during carbonation, severely affecting the purity of calcium carbonate. Furthermore, improper control of carbonation time can also lead to Mg... 2+ Co-precipitation introduces magnesium carbonate impurities, further affecting product purity. Chinese patent application CN120328599A discloses a method for synergistically utilizing magnesium smelting byproducts to prepare light calcium carbonate and molecular sieves. This method uses ammonia to capture carbon dioxide from magnesium smelting flue gas to prepare ammonium bicarbonate, then uses ammonium chloride solution to leach magnesium slag to obtain a leachate, and finally uses the ammonium bicarbonate and leachate to prepare calcium carbonate. However, this single ammonium leaching method results in some calcium in the magnesium slag being encapsulated by silicates or stored in a relatively stable phase, making complete calcium extraction difficult in a single leaching, leading to a low calcium recovery rate. Furthermore, the method does not address the lack of treatment of Al in the leachate. 3+ Fe 3+Impurity ions must be effectively removed, as these impurities co-precipitate into the product during carbonation, severely affecting the purity of calcium carbonate. Chinese patent CN120099291B discloses a high-efficiency, low-consumption leaching method for smelting slag based on ammonium salt leaching agent recycling, using multi-stage countercurrent leaching with ammonium salt solution to obtain a calcium-rich leachate. Although multi-stage countercurrent leaching is involved, its design purpose is primarily to achieve the recycling of the leaching agent, rather than to address the problem of calcium in magnesium slag being difficult to extract completely due to silicate encapsulation. When some calcium in magnesium slag is encapsulated by silicates or stored in relatively stable phases, a single leaching in this process is insufficient to completely extract calcium, resulting in a low calcium recovery rate. In summary, in traditional single-stage ammonium leaching processes, some calcium in magnesium slag is encapsulated by silicates or stored in relatively stable phases, making it difficult to completely extract calcium in a single leaching, leading to a low calcium recovery rate and low calcium carbonate yield. Residual Al in the leachate... 3+ Fe 3+ Impurity ions can co-precipitate into the calcium carbonate product during carbonation, severely affecting product purity. Currently, the purity of calcium carbonate prepared by a single ammonium leaching process is typically below 97%. Magnesium slag contains various elements besides calcium, such as Mg, Fe, and Al; the migration and distribution patterns of these impurities during the ammonium leaching-carbonation process are still unclear. If the carbonation time is too short, Ca... 2+ Incomplete precipitation; as carbonization proceeds, the solution pH gradually decreases, and when the pH drops below a certain threshold, Mg... 2 + It initially co-precipitates as magnesium carbonate, leading to a decrease in purity.

[0004] To address the shortcomings of the existing technologies, a method is needed to prepare high-purity light calcium carbonate using recycled ammonium leaching of magnesium slag, thereby improving the calcium extraction rate and removing Al from the leachate. 3+ Fe 3+ Impurities such as Mg are avoided by precisely controlling the carbonization time. 2+ Co-precipitation is performed to obtain a high-purity, light calcium carbonate product. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for preparing calcium carbonate using magnesium slag recycling ammonium leaching and calcium carbonate, so as to solve the technical problems of low calcium extraction rate, low product purity caused by co-precipitation of impurity ions, and the impact of magnesium ion co-precipitation on product purity during the carbonation process in the existing single ammonium leaching process.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag, comprising the following steps: 1) Add water to the pretreated magnesium slag to carry out a digestion reaction; 2) The digested material is subjected to ammonium leaching reaction. After solid-liquid separation, primary leachate and primary leachate residue are obtained. 3) Perform at least one cycle of ammonium leaching reaction on the primary leaching residue. After solid-liquid separation, obtain the circulating leachate. Combine the primary leachate and all circulating leachates to obtain the mixed leachate. 4) Adjust the pH of the mixed leachate to 10-11, then add an alkaline solution for purification. After solid-liquid separation, the purified solution is obtained. 5) Carbon dioxide is introduced into the purified liquid to carry out a carbonization reaction. After filtration, washing, and drying, calcium carbonate is obtained.

[0007] Preferably, in step 1), the temperature of the digestion reaction is 40-60℃ and the time is 30-50 min; the liquid-solid ratio of the pretreated magnesium slag to deionized water is (15-25):1.

[0008] Preferably, in step 1), the pretreatment step of magnesium slag is as follows: drying the magnesium slag at 105-120℃ for 6-12 h, grinding it and passing it through a 150-mesh sieve.

[0009] Preferably, in steps 2) and 3), the ammonium leaching reaction conditions are: an addition concentration of 1.5-2.5 mol·L⁻¹ -1 The reaction temperature of ammonium chloride is 40-60℃, and the reaction time is 30-50 min.

[0010] Preferably, in step 3), the number of times the cyclic ammonium leaching reaction is performed is one, that is, the leaching residue is subjected to one cyclic ammonium leaching to obtain a secondary leachate.

[0011] Preferably, in step 4), ammonia is added to adjust the pH of the mixed leachate to 10-11.

[0012] Preferably, in step 4), the alkaline solution is a sodium hydroxide solution, and the purification conditions are: an addition concentration of 0.5-1.5 mol·L⁻¹ -1 After adding sodium hydroxide solution, let it stand for 10-15 minutes.

[0013] Preferably, in step 5), the carbonization reaction temperature is 30-60℃, the carbonization reaction time is 9-12 min, and the carbon dioxide flow rate is 100-300 mL·min. -1 .

[0014] Preferably, in step 5), the drying temperature is 105-120℃.

[0015] The present invention also discloses a calcium carbonate prepared by the above-mentioned method of preparing calcium carbonate by circulating ammonium leaching of magnesium slag. In the calcium carbonate, the mass fraction of calcium carbonate is ≥98.5% and the mass fraction of MgO is ≤0.03%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing calcium carbonate using cyclic ammonium leaching of magnesium slag. In the calcium extraction stage, addressing the problem that some calcium in the magnesium slag is encapsulated by silicates or exists as a stable phase, making complete extraction difficult in a single leaching, this invention performs at least one cyclic ammonium leaching reaction on the leaching residue after the first ammonium leaching. This further dissolves the residual calcium, and the first leaching solution is combined with all cyclic leaching solutions, thereby significantly improving the total calcium leaching rate from the magnesium slag. In the impurity removal stage, addressing the issue of residual Al in the leaching solution obtained from the first ammonium leaching... 3+ Fe 3+ To address the defect that impurity ions can co-precipitate into the product during subsequent carbonization, severely affecting product purity, this invention introduces a purification step before the carbonization reaction. First, the pH of the mixed leachate is adjusted to 10-11 to create alkaline conditions for impurity precipitation. Then, an alkaline solution is added to allow Al to precipitate. 3+ and Fe 3+ Impurities precipitate as hydroxides, and are removed from the system beforehand through solid-liquid separation, fundamentally blocking their path into the final product. The MgO mass fraction in Example 1 is only 0.028%, far lower than the 0.058% in Comparative Example 1, fully demonstrating the crucial role of purification in improving product purity. In the carbonation reaction stage, carbon dioxide is introduced into the purified liquid to initiate the carbonation reaction, generating calcium carbonate. This achieves a complete transformation from industrial solid waste magnesium slag to high-purity calcium carbonate. The process conditions are mild, requiring no high-temperature or high-pressure equipment, and offer the dual benefits of solid waste resource utilization and high-value product preparation.

[0017] The calcium carbonate produced by the above-disclosed method for preparing calcium carbonate using cyclic ammonium leaching of magnesium slag, through the synergistic effect of cyclic ammonium leaching, leachate purification, and carbonation, yields a high-purity calcium carbonate product that cannot be achieved by existing single-stage ammonium leaching processes. SEM images and EDS analysis show that the product is regular cubic calcite with complete crystallization and good dispersibility. The XRD pattern shows no characteristic peaks of magnesium carbonate impurities, further confirming the high quality of the calcium carbonate product. This product is prepared from bulk industrial solid waste magnesium reduction slag using the cyclic ammonium leaching and purification process of this invention. While achieving high-value utilization of solid waste, the resulting calcium carbonate product has high purity and stable quality, meeting the quality requirements of higher-end application fields for calcium carbonate raw materials. Attached Figure Description

[0018] Figure 1 This is a process flow diagram of the present invention for preparing high-purity light calcium carbonate using magnesium slag; Figure 2 Raman spectra of calcium carbonate products with different carbonation times according to this invention; Figure 3The XRD patterns of calcium carbonate products obtained at different carbonation times according to the present invention are compared; where (a) is carbonized for 9 min; (b) is carbonized for 6 min; (c) is carbonized for 12 min; and (d) is carbonized for 15 min. Figure 4 The images shown are SEM images of the calcium carbonate product obtained in Example 1 of this invention; where (a) represents 100k; (b) represents 50k; (c) represents 20k; and (d) represents 10k. Figure 5 EDS energy dispersive spectroscopy analysis of the calcium carbonate products obtained in Examples 1, 2, 2 and 3 of this invention; wherein, (a) carbonation for 9 min; (b) carbonation for 6 min; (c) carbonation for 12 min; and (d) carbonation for 15 min. Detailed Implementation

[0019] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0021] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0022] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0023] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0024] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.

[0025] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0026] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0027] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0028] This invention provides a method for preparing high-purity light calcium carbonate using recycled ammonium leaching of magnesium slag, comprising the following steps: (a) Raw material pretreatment Magnesium slag was placed in a drying oven and dried at 105-120℃ for 6-12 hours. The dried magnesium slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the portion passing through the sieve was collected as experimental material.

[0029] (ii) Digestion reaction Weigh out the pretreated magnesium slag and place it in a beaker. Add deionized water (liquid-to-solid ratio approximately (15-25):1). Stir the mixture at 40-60℃ for 30-50 min to fully hydrate the free CaO in the magnesium slag to form Ca(OH)2. The reaction equation is as follows: CaO + H₂O → Ca(OH)₂ (iii) Primary ammonium leaching Add solid NH4Cl to the digested system (to make the NH4Cl concentration approximately 1.5-2.5 mol·L⁻¹). -1 The mixture was stirred at 40-60℃ for 30-50 min. The reaction equation is as follows: Ca(OH)2+2NH4Cl→CaCl2+2NH3·H2O After the reaction was completed, vacuum filtration (solid-liquid separation) was performed to obtain a primary leachate containing CaCl2 and a primary leachate residue.

[0030] (iv) Secondary ammonium leaching (In this invention, cyclic ammonium leaching refers to ammonium leaching of the previous leaching residue again; secondary ammonium leaching indicates that the cycle is once.) Transfer the primary leaching residue to a beaker, add deionized water, and then add NH4Cl solid (maintaining a concentration of 1.5-2.5 mol·L⁻¹). -1 (Concentration), and stir the reaction at 40-60℃ for 30-50 min to further dissolve the residual calcium. The reaction equation is as follows: Ca(OH)₂ (in residue) + 2NH₄Cl → CaCl₂ + 2NH₃·H₂O After the reaction was completed, the solution was filtered under vacuum to obtain a secondary leachate containing CaCl2. The secondary leachate residue was discarded as waste.

[0031] (v) Leachate Consolidation and Purification Treatment Combine the primary and secondary leachates and stir thoroughly. Slowly add ammonia (NH3·H2O) to the combined leachate to adjust the pH to 10-11. The addition of ammonia serves two purposes: firstly, to provide NH3·H2O for the subsequent carbonization reaction; and secondly, to provide a suitable environment for Al2O3 production. 3+ Fe 3+ The precipitation creates alkaline conditions.

[0032] Add sodium hydroxide (NaOH) solution (concentration approximately 0.5-1.5 mol·L⁻¹) to the pH-adjusted solution. -1 Under alkaline conditions (pH≥10), Al 3+ and Fe 3+ Al(OH)3 and Fe(OH)3 precipitates are formed: Al 3+ +3OH - →Al(OH)3↓ Fe 3+ +3OH - →Fe(OH)3↓ Let stand for 10-15 minutes to allow complete precipitation. Remove the precipitate by vacuum filtration to obtain a purified clear liquid, which mainly contains CaCl2 and NH3·H2O.

[0033] (vi) Carbonization reaction Place the purified solution in a reaction vessel and maintain the temperature at 30-60℃. Introduce CO2 gas into the solution at a flow rate of 100-300 mL / min. -1 (While stirring, the carbonization reaction is carried out.) The carbonization reaction equation is as follows: CaCl2+2NH3·H2O+CO2→CaCO3↓+2NH4Cl+H2O The carbonization time is controlled at 9-12 min (preferably 9 min), and the final pH value is approximately 9.

[0034] During the carbonization process, the pH value of the solution is monitored in real time using an online pH meter. When the pH value drops to about 9, the CO2 is stopped, and the corresponding carbonization time is 9~12 min.

[0035] After carbonization, the product is filtered, washed, and dried at 105-120℃ to obtain a light calcium carbonate product.

[0036] (vii) Precise control of carbonization time like Figure 2-5 As shown, carbonization time has a significant impact on product purity: When carbonization time is <9 min: Ca 2+ The precipitation was incomplete, and the product was mainly metastable spheroidal aragonite with low crystallinity, purity, and yield.

[0037] When the carbonization time is 9~12 min: Ca 2+ The crystals are almost completely precipitated, and the crystal form is completely transformed into thermodynamically stable calcite. The crystals are well-developed, highly crystallized, and the product purity and yield are both optimal.

[0038] When carbonization time > 12 min: Mg 2+ Initially, it precipitates as magnesium carbonate, and X-ray diffraction (XRD) detects characteristic peaks of MgCO3 (2θ≈30.7°, 41.2°). At the same time, some CaCO3 reacts with excess CO2 to form soluble Ca(HCO3)2, and the purity of the product decreases significantly.

[0039] Therefore, the carbonization time should be strictly controlled within 9 to 12 minutes, with 9 minutes being the preferred time.

[0040] Advantages of this invention: 1. High calcium extraction rate: A multi-stage ammonium leaching process is used to further treat the primary leaching residue, allowing residual calcium to dissolve further. The combined leaching solutions from both processes significantly increase the total calcium ion concentration, effectively improving the calcium carbonate yield. 2. High product purity: The pH is adjusted to 10-11 with ammonia, and NaOH is added to precipitate Al. 3+ Fe 3+ This effectively removes impurity ions from the leachate. After a second ammonium leaching optimization treatment, the calcium carbonate product obtained by this invention has a calcium carbonate mass fraction of 98.532%; the magnesium impurity content (calculated as MgO) is only 0.028%. 3. Precise and controllable carbonation time: The optimal carbonation time was determined to be 9~12 min (preferably 9 min), at which point the product's relative crystallinity reaches 100% and its purity reaches 98.532%. Too short or too long a carbonation time will lead to a decrease in purity. 4. Stable product quality: By controlling the carbonation time to 9~12 min, the impurity ions in the MgO are effectively avoided. 2+ Co-precipitation (XRD shows no MgCO3 impurity peak), the product is regular cubic calcite with good dispersibility. 5. Mild process conditions: Ammonium leaching is carried out at 40-60℃ and normal pressure, and carbonation is carried out at 30-60℃ and normal pressure, requiring no high-temperature and high-pressure equipment, resulting in low energy consumption. 6. Solid waste resource utilization: High-value-added light calcium carbonate is prepared from magnesium slag, realizing the high-value utilization of magnesium slag and solving the environmental problems caused by magnesium slag stockpiling. The obtained high-purity calcium carbonate product can be used in pharmaceuticals, food, coatings, plastics, rubber, and other fields with high requirements for calcium carbonate purity.

[0041] The technical problems to be solved by this invention are: 1. To provide a method for extracting calcium from magnesium slag using a multi-stage ammonium leaching process, which improves the total leaching rate of calcium and the yield of calcium carbonate through multi-stage countercurrent leaching. 2. To provide a method for purifying the leachate, which removes Al by adjusting the pH with ammonia water and precipitating sodium hydroxide. 3+ Fe3+ Impurity ions are removed to improve the purity of the final product. 3. A method for precise control of carbonization time is provided to avoid Mg... 2+ 4. Co-precipitation ensures product purity. This study reveals the quantitative relationship between the number of ammonium leaching cycles and product purity, providing a theoretical basis for process optimization.

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0043] Example 1 (Secondary ammonium leaching, purification treatment, carbonization time 9 min) Magnesium slag was placed in a drying oven and dried at 105℃ for 12 h. The dried slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the undersize portion was collected as experimental material. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 20:1. The mixture was stirred at 50℃ for 40 min to fully hydrate the free CaO in the slag to form Ca(OH)₂. Solid NH₄Cl was added to the digested system to a concentration of approximately 2.0 mol·L⁻¹. -1 The mixture was stirred at 60℃ for 40 min to perform the first ammonium leaching. After the reaction was completed, it was filtered under vacuum to obtain a primary leaching solution containing CaCl2 and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.0 mol·L⁻¹). -1 The solution was stirred at 60℃ for 40 min to perform a second ammonium leaching, further dissolving the residual calcium. After the reaction, the solution was vacuum filtered to obtain a secondary leachate containing CaCl2, and the secondary leachate residue was discarded as waste. The two leachates were combined and stirred thoroughly. Ammonia was slowly added to the combined leachate to adjust the pH to 10-11, and 1 mol / L NaOH was added to precipitate Al. 3+ Fe 3+ After static filtration, the purified liquid was kept at a temperature of 30℃ and CO2 gas was introduced at a flow rate of 200 mL / min. -1The carbonation time was 9 minutes. The product was filtered, washed, and dried at 105℃ to obtain calcium carbonate. X-ray fluorescence spectrometry (XRF) analysis showed a calcium carbonate content of 98.532% and an MgO mass fraction of 0.028%.

[0044] Example 2 (Secondary ammonium leaching, purification treatment, carbonization time 12 min) Magnesium slag was placed in a drying oven and dried at 105℃ for 12 h. The dried slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the undersize portion was collected as experimental material. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 20:1. The mixture was stirred at 50℃ for 40 min to fully hydrate the free CaO in the slag to form Ca(OH)₂. Solid NH₄Cl was added to the digested system to a concentration of approximately 2.0 mol·L⁻¹. -1 The mixture was stirred at 60℃ for 40 min to perform the first ammonium leaching. After the reaction was completed, it was filtered under vacuum to obtain a primary leaching solution containing CaCl2 and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.0 mol·L⁻¹). -1 The solution was stirred at 60℃ for 40 min to perform a second ammonium leaching, further dissolving the residual calcium. After the reaction, the solution was vacuum filtered to obtain a secondary leachate containing CaCl2, and the secondary leachate residue was discarded as waste. The two leachates were combined and stirred thoroughly. Ammonia was slowly added to the combined leachate to adjust the pH to 10-11, and 1 mol / L NaOH was added to precipitate Al. 3+ Fe 3+ After static filtration, the purified liquid was kept at a temperature of 30°C and CO2 gas was introduced at a flow rate of 200 mL / min. -1 The carbonation time was 12 min. The product was filtered, washed, and dried at 105℃ to obtain calcium carbonate. XRD analysis showed the product to be calcite-type calcium carbonate, and X-ray fluorescence spectroscopy (XRF) analysis determined the purity to be 96.8%.

[0045] Example 3 (Secondary ammonium leaching, purification treatment, reaction time 30 min) Magnesium slag was placed in a drying oven and dried at 105℃ for 12 h. The dried slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the undersize portion was collected as experimental material. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 20:1. The mixture was stirred at 50℃ for 30 min (digestion time) to fully hydrate the free CaO in the slag to form Ca(OH)₂. Solid NH₄Cl was added to the digested system to a concentration of approximately 2.0 mol·L⁻¹. -1The mixture was stirred at 60℃ for 30 min (the time for the first ammonium leaching) to perform the first ammonium leaching. After the reaction, it was vacuum filtered to obtain a primary leaching solution containing CaCl2 and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.0 mol·L⁻¹). -1 The concentration was adjusted, and the mixture was stirred at 60℃ for 30 min (secondary ammonium leaching time) to further dissolve the residual calcium. After the reaction, the mixture was vacuum filtered to obtain a secondary leaching solution containing CaCl2, and the secondary leaching residue was discarded as waste. The two leaching solutions were combined and stirred thoroughly. Ammonia water was slowly added to the combined leaching solution to adjust the pH to 10-11, and 1 mol / L NaOH was added to precipitate Al. 3+ Fe 3+ After static filtration, the purified liquid was kept at a temperature of 30°C and CO2 gas was introduced at a flow rate of 200 mL / min. -1 The carbonation time was 9 min. The product was filtered, washed, and dried at 105℃ to obtain calcium carbonate. XRD analysis showed the product to be calcite-type calcium carbonate, and X-ray fluorescence spectrometry (XRF) analysis determined the purity to be 97.8%.

[0046] Example 4 (Secondary ammonium leaching, purification treatment, reaction time 50 min) Magnesium slag was placed in a drying oven and dried at 105℃ for 12 h. The dried slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the undersize portion was collected as experimental material. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 20:1. The mixture was stirred at 50℃ for 50 min (digestion time) to fully hydrate the free CaO in the slag to form Ca(OH)₂. Solid NH₄Cl was added to the digested system to a concentration of approximately 2.0 mol·L⁻¹. -1 The mixture was stirred at 60℃ for 50 min (the time for the first ammonium leaching) to perform the first ammonium leaching. After the reaction, it was filtered under vacuum to obtain a primary leaching solution containing CaCl2 and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.0 mol·L⁻¹). -1 The concentration was adjusted, and the mixture was stirred at 60℃ for 50 min (secondary ammonium leaching time) to further dissolve the residual calcium. After the reaction, the mixture was vacuum filtered to obtain a secondary leachate containing CaCl2, and the secondary leachate residue was discarded as waste. The two leachates were combined and stirred thoroughly. Ammonia water was slowly added to the combined leachate to adjust the pH to 10-11, and 1 mol / L NaOH was added to precipitate Al. 3+ Fe 3+ After static filtration, the purified liquid was kept at a temperature of 30°C and CO2 gas was introduced at a flow rate of 200 mL / min.-1 The carbonation time was 9 min. The product was filtered, washed, and dried at 105℃ to obtain calcium carbonate. XRD analysis showed the product to be calcite-type calcium carbonate, and X-ray fluorescence spectrometry (XRF) analysis determined the purity to be 98.4%.

[0047] Example 5 (Secondary ammonium leaching, purification treatment, reaction temperature 40℃) Magnesium slag was placed in a drying oven and dried at 105℃ for 12 h. The dried slag was then ground and passed through a 150-mesh standard sieve (0.355 mm aperture), and the undersize portion was collected as experimental material. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 20:1. The mixture was stirred and reacted at 40℃ for 40 min (digestion temperature) to fully hydrate the free CaO in the slag to form Ca(OH)₂. Solid NH₄Cl was added to the digested system to a concentration of approximately 2.0 mol·L⁻¹. -1 The mixture was stirred at 40℃ for 40 min (the temperature for the first ammonium leaching) to perform the first ammonium leaching. After the reaction, it was filtered under vacuum to obtain a primary leaching solution containing CaCl2 and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.0 mol·L⁻¹). -1 The concentration was adjusted, and the mixture was stirred at 40℃ for 40 min (secondary ammonium leaching temperature) to further dissolve the residual calcium. After the reaction, the mixture was vacuum filtered to obtain a secondary leaching solution containing CaCl2, and the secondary leaching residue was discarded as waste. The two leaching solutions were combined and stirred thoroughly. Ammonia water was slowly added to the combined leaching solution to adjust the pH to 10-11, and 1 mol / L NaOH was added to precipitate Al. 3+ Fe 3+ After static filtration, the purified liquid was kept at a temperature of 30°C and CO2 gas was introduced at a flow rate of 200 mL / min. -1 The carbonation time was 9 min. The product was filtered, washed, and dried at 105℃ to obtain calcium carbonate. XRD analysis showed the product to be calcite-type calcium carbonate, and X-ray fluorescence spectrometry (XRF) analysis determined the purity to be 97.2%.

[0048] Although the product purity was slightly lower at 40℃, it was still much higher than that of the single ammonium leaching scheme of Comparative Example 1 (96.745%), and the purity could be further improved by appropriately extending the reaction time (e.g., from 40 min to 50 min).

[0049] Example 6 (liquid-solid ratio 15:1, NH4Cl concentration 1.5 mol / L, carbonization time 10 min, carbonization temperature 45℃, CO2 flow rate 100 mL / min, NaOH concentration 0.5 mol / L, standing for 10 min) Magnesium slag was placed in a drying oven and dried at 110℃ for 9 h. The dried slag was then ground and passed through a 150-mesh standard sieve. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 15:1. The mixture was stirred and reacted at 50℃ for 40 min. Solid NH4Cl was added to the digested system to make a concentration of approximately 1.5 mol·L⁻¹. -1 The mixture was stirred at 50°C for 40 min to perform the first ammonium leaching. Vacuum filtration was then performed to obtain a primary leaching solution and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 1.5 mol·L⁻¹). -1 The ammonium solution was stirred at 50℃ for 40 min for a second ammonium leaching, followed by vacuum filtration to obtain a second leachate. The two leachates were combined. Ammonia solution with a concentration of 0.5 mol·L⁻¹ was slowly added to the combined leachate to adjust the pH to 10-11. -1 NaOH solution precipitates Al 3+ Fe 3+ Let stand for 10 minutes, then filter. Maintain the temperature of the purified liquid at 45℃ and introduce CO2 gas at a flow rate of 100 mL / min. -1 The carbonation time was 10 min. After filtration, washing, and drying at 110℃, calcium carbonate product was obtained.

[0050] Example 7 (liquid-solid ratio 25:1, NH4Cl concentration 2.5 mol / L, carbonization time 11 min, carbonization temperature 50℃, CO2 flow rate 300 mL / min, NaOH concentration 1.5 mol / L, standing for 15 min) Magnesium slag was placed in a drying oven and dried at 120℃ for 6 h. The dried slag was then ground and passed through a 150-mesh standard sieve. 15.00 g of the pretreated slag was taken and added to deionized water to make a liquid-to-solid ratio of 25:1. The mixture was stirred and reacted at 50℃ for 40 min. Solid NH4Cl was added to the digested system to make a concentration of approximately 2.5 mol·L⁻¹. -1 The mixture was stirred at 50°C for 40 min to perform the first ammonium leaching. Vacuum filtration was then performed to obtain a primary leaching solution and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and solid NH4Cl was added (maintaining a concentration of 2.5 mol·L⁻¹). -1 The mixture was stirred at 50℃ for 40 min to perform a second ammonium leaching, followed by vacuum filtration to obtain a secondary leachate. The two leachates were combined. Ammonia solution was slowly added to the combined leachate to adjust the pH to 10-11, with a concentration of 1.5 mol·L⁻¹. -1 NaOH solution precipitates Al 3+ Fe 3+Let stand for 15 minutes, then filter. Maintain the temperature of the purified liquid at 50℃ and introduce CO2 gas at a flow rate of 300 mL / min. -1 The carbonation time was 11 min. After filtration, washing, and drying at 120℃, calcium carbonate product was obtained.

[0051] Example 8 (Three-cycle ammonium leaching) Magnesium slag was placed in a drying oven and dried at 110℃ for 9 h. The dried magnesium slag was then ground and passed through a 150-mesh standard sieve. 15.00 g of the pretreated magnesium slag was taken and added to deionized water at a liquid-to-solid ratio of 20:1, and the mixture was stirred at 50℃ for 40 min. 2.0 mol·L⁻¹ NH₄Cl solid was then added to the digested system. -1 The mixture was stirred at 50°C for 40 min to perform a first ammonium leaching, followed by vacuum filtration to obtain a primary leaching solution and a primary leaching residue. The primary leaching residue was transferred to a beaker, deionized water was added, and 2.0 mol·L⁻¹ NH₄Cl solid was added. -1 The mixture was stirred at 50°C for 40 min to perform a second ammonium leaching. Vacuum filtration was then performed to obtain a secondary leaching solution and a secondary leaching residue. The secondary leaching residue was transferred back to a beaker, deionized water was added, and 2.0 mol·L⁻¹ NH₄Cl solid was added. -1 The mixture was stirred at 50℃ for 40 min, followed by a third ammonium leaching. The mixture was then vacuum filtered to obtain three leachates. The three leachates were combined. Ammonia was slowly added to the combined leachate to adjust the pH to 10-11, and then 1.0 mol·L⁻¹ of ammonia solution was added. -1 NaOH solution precipitates Al 3+ Fe 3+ Let stand for 12 minutes, then filter. Maintain the temperature of the purified liquid at 40℃ and purge with CO2 gas (flow rate 200 mL / min). -1 The carbonation time was 10 min. After filtration, washing, and drying at 110℃, calcium carbonate product was obtained.

[0052] Comparative Example 1 (Single Ammonium Leaching) Take 15.00 g of pretreated magnesium slag, add 300 mL of deionized water, and digest at 50℃ for 40 min. Add 21.40 g of NH4Cl, and stir at 60℃ for 40 min. Filter, and the filtrate is directly carbonized with CO2 for 12 min without purification. Filter, wash, and dry to obtain calcium carbonate product. XRF determination shows that the mass fraction of calcium carbonate is 96.745%, and the mass fraction of MgO is 0.058%.

[0053] In Comparative Example 1, the effects of the number of ammonium leaching cycles and the filtrate purification process on the quality of calcium carbonate products were compared using single variables to verify the technical advantages of the two-stage ammonium leaching coupled with impurity purification. Compared to the two-stage ammonium leaching + purification process in Example 1, this group only used a single ammonium leaching without purifying the leachate, resulting in a calcium carbonate product with a purity of only 96.745%, which is lower in purity and higher in impurity content. The presence of impurity ions in the unpurified leachate affects the carbonation reaction. This demonstrates that a single ammonium leaching cannot fully dissolve the residual calcium components in the magnesium slag, and the unpurified leachate contains a large amount of impurities such as magnesium, aluminum, and iron, severely reducing product purity. The two-stage ammonium leaching combined with acid-base purification can effectively improve calcium utilization and product purity while reducing impurity content.

[0054] Comparative Example 2 (Secondary ammonium leaching, purification treatment, carbonization time 15 min) The procedure was the same as in Example 1, except the carbonization time was changed to 15 min. XRD analysis showed characteristic peaks of MgCO3 at 2θ≈30.7° and 41.2°, indicating that the purity had decreased to 94.5%.

[0055] In Comparative Example 2, the effect of excessively long carbonation time on the crystal form and purity of calcium carbonate products was investigated to determine the optimal upper limit of carbonation time. Compared to the optimal carbonation time of 9 min in Example 1, after extending the carbonation time to 15 min, the XRD pattern of the product showed characteristic diffraction peaks of magnesium carbonate, indicating the co-precipitation of a large amount of magnesium impurities, resulting in a significant decrease in the purity of the calcium carbonate product to 94.5%. This demonstrates that excessively long carbonation time promotes the continuous deposition of magnesium ions in the system, forming magnesium carbonate impurities, which damages product purity. Therefore, excessively long carbonation time is detrimental to the preparation of high-quality calcium carbonate.

[0056] Comparative Example 3 (Secondary ammonium leaching, purification treatment, carbonization time 6 min) The procedure was the same as in Example 1, except the carbonization time was changed to 6 min. XRD analysis showed that the product was mainly metastable spheroidal aragonite, with a crystallinity of only 82.8% and an EDS calcium content of 30.2%.

[0057] In Comparative Example 3, the effects of excessively short carbonation time on the crystal form, crystallinity, and composition of calcium carbonate were investigated to determine the optimal lower limit of carbonation time. When the carbonation time was shortened to 6 min, the EDS calcium content was only 30.2%, which was significantly different from the theoretical value. The main reason was insufficient time, leaving a considerable amount of calcium in the solution. 2+ If it fails to settle completely, unreacted Ca(OH)2 or crystalline hydrates may remain in the product; at the same time, the metastable aragonite itself has a less dense crystal structure, making it more prone to carrying impurities.

[0058] Comparative Example 4 (secondary ammonium leaching, purification treatment, carbonization time 9 min, carbonization temperature 40℃) The procedure was the same as in Example 1, except the carbonation time was changed to 9 minutes. XRD analysis showed that the product was calcite-type calcium carbonate with a purity of 97.98%.

[0059] In Comparative Example 4, the effect of a lower carbonation temperature on the purity of calcium carbonate was investigated using a single variable, verifying the process advantages of carbonation at room temperature (30℃). While keeping other optimal process parameters unchanged, increasing the carbonation temperature from 30℃ to 40℃ resulted in a product that, although still in its pure calcite crystal form, had a purity reduced to 97.98%, lower than the optimal purity of Example 1. This demonstrates that moderately low-temperature carbonation is more conducive to the formation of high-purity calcium carbonate, and a slight increase in temperature will slightly affect the selectivity of the carbonation precipitation reaction, leading to a decrease in product purity.

[0060] Comparative Example 5 (secondary ammonium leaching, purification treatment, carbonization time 9 min, carbonization temperature 60℃) The procedure was the same as in Example 1, except the carbonation time was changed to 9 minutes. XRD analysis showed that the product was calcite-type calcium carbonate with a purity of 97.78%.

[0061] In Comparative Example 5, the influence of high-temperature carbonation conditions on the purity of calcium carbonate products was investigated, and the suitable range of carbonation temperature was determined. When the carbonation temperature was increased to 60℃, the product still maintained the calcite crystal form, but the purity further decreased to 97.78%. As the carbonation temperature increased, the purity of calcium carbonate products showed a continuous downward trend. High-temperature conditions easily induce side reactions and promote the co-precipitation of trace impurities, which is not conducive to the preparation of ultra-high purity calcium carbonate products. Low-temperature and mild carbonation is the optimal process condition.

[0062] Figure 1 This is a process flow diagram of the preparation of high-purity light calcium carbonate from magnesium slag according to the present invention. The process includes steps such as digestion reaction, primary ammonium leaching, secondary ammonium leaching, leaching solution merging and purification, and carbonation reaction. As shown in the diagram, the method for preparing high-purity light calcium carbonate from magnesium slag according to the present invention includes: the magnesium slag is first digested to hydrate free CaO into Ca(OH)2, and then subjected to two separate ammonium chloride leaching processes (primary ammonium leaching and secondary ammonium leaching). After filtration, primary leaching solution, primary leaching residue, secondary leaching solution, and secondary leaching residue are obtained. The primary leaching residue is used as raw material for secondary ammonium leaching to further improve the total calcium extraction rate, while the secondary leaching residue is discarded as waste. The primary and secondary leaching solutions are combined, and ammonia water is added sequentially to adjust the pH to 10-11, and sodium hydroxide is added to precipitate Al. 3+ Fe 3+ The mixture is allowed to stand and filtered to remove impurities and precipitates, resulting in a purified clear liquid. Finally, CO2 is introduced into the clear liquid to carry out a carbonization reaction. After filtration, washing, and drying, a high-purity light calcium carbonate product is obtained.

[0063] Figure 2The figures show the Raman spectra of calcium carbonate products with different carbonation times according to this invention. As can be seen from the figures, the Raman peak is strongest at a carbonation time of 9 minutes, which is the optimal carbonation time.

[0064] Figure 3 The XRD patterns of calcium carbonate products obtained by different carbonation times in this invention are compared; (a) represents 9 min of carbonation; (b) represents 6 min of carbonation; (c) represents 12 min of carbonation; and (d) represents 15 min of carbonation. It can be seen from the figure that calcite is pure phase at 9 min and MgCO3 impurity peak appears at 15 min.

[0065] Figure 4 The image shows a scanning electron microscope (SEM) image of the calcium carbonate product obtained in Example 1 of this invention; where (a) is 100k; (b) is 50k; (c) is 20k; and (d) is 10k. As can be seen from the image, the calcite is regular cubic and has good dispersibility.

[0066] Figure 5 EDS energy dispersive spectroscopy analysis of calcium carbonate products obtained in Examples 1, 2, 2 and 3 of this invention; wherein, (a) carbonation for 9 min; (b) carbonation for 6 min; (c) carbonation for 12 min; (d) carbonation for 15 min; it can be seen from the figure that this sample mainly contains calcium carbonate and magnesium hydroxide.

[0067] In summary, this invention provides a method for preparing calcium carbonate using cyclic ammonium leaching of magnesium slag, and the calcium carbonate itself. Using magnesium reduction slag from the Pidgeon process as raw material, the method comprises the following steps: First, the magnesium slag undergoes a digestion reaction to fully hydrate the free calcium oxide in the slag to generate calcium hydroxide; then, ammonium chloride is added to the digested system for a primary ammonium leaching reaction, followed by solid-liquid separation to obtain a primary leachate and a primary leaching residue; for residual calcium that was not dissolved due to silicate encapsulation or its presence as a stable phase during the primary ammonium leaching, this invention performs at least one cyclic ammonium leaching reaction on the primary leaching residue to further dissolve this difficult-to-extract calcium, followed by solid-liquid separation to obtain a circulating leachate; finally, the primary leachate is combined with all circulating leachates to obtain a mixed leachate, thereby... This invention significantly improves the total calcium leaching rate and the final calcium carbonate product yield from magnesium slag. Before the carbonation reaction, the mixed leachate undergoes targeted purification treatment. First, ammonia is added to adjust the pH, creating alkaline conditions for impurity precipitation and providing ammonia for the subsequent carbonation reaction. Then, sodium hydroxide solution is added, causing residual aluminum and iron ions in the leachate to precipitate as aluminum hydroxide and iron hydroxide, respectively. After solid-liquid separation, a purified solution is obtained, thus pre-removing these impurity ions that would co-precipitate into the product during carbonation, effectively ensuring the purity of the final product. Finally, carbon dioxide is introduced into the purified solution for carbonation, generating calcium carbonate precipitate. After filtration, washing, and drying, a light calcium carbonate product is obtained. This invention employs a circulating ammonium leaching process to treat the primary leaching residue multiple times, breaking the limitations of traditional primary leaching processes on calcium extraction rates. This allows for the full dissolution of calcium with complex forms in magnesium slag, significantly improving the total calcium leaching rate and effectively increasing the calcium carbonate yield. By employing ammonia pH adjustment and sodium hydroxide precipitation purification steps in the leaching solution, impurity ions such as aluminum and iron are pre-separated and removed as hydroxide precipitates before carbonation. This fundamentally solves the problem of low product purity caused by impurity co-precipitation. Experimental verification shows that the final calcium carbonate product contains 98.532% calcium carbonate and only 0.028% magnesium oxide, with purity far superior to existing single-stage ammonium leaching processes. During the carbonation reaction, precisely controlling the carbonation time to 9-12 minutes ensures complete precipitation of calcium ions, transforming the product's crystal form into thermodynamically stable cubic calcite with high crystallinity and good dispersibility. It also effectively avoids the problem of magnesium ions co-precipitating as magnesium carbonate due to excessively long carbonation times, and the product loss caused by the reaction of some calcium carbonate with excess carbon dioxide to form soluble calcium bicarbonate. The product's X-ray diffraction pattern shows no characteristic peaks of magnesium carbonate impurities, reliably guaranteeing purity and quality. The entire process of this invention is carried out under normal pressure and low temperature conditions, eliminating the need for high-temperature and high-pressure equipment. The process conditions are mild, the operation is simple, and energy consumption is low, making it promising for industrial application.Using magnesium reduction slag, a bulk industrial solid waste, as raw material, high-value-added light calcium carbonate products are produced. While realizing the resource utilization and high-value utilization of solid waste, it effectively alleviates the land occupation and environmental pollution problems caused by the long-term stockpiling of magnesium slag, thus achieving both economic and environmental benefits.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag, characterized in that, Includes the following steps: 1) Add water to the pretreated magnesium slag to carry out a digestion reaction; 2) The digested material is subjected to ammonium leaching reaction. After solid-liquid separation, primary leachate and primary leachate residue are obtained. 3) Perform at least one cycle of ammonium leaching reaction on the primary leaching residue. After solid-liquid separation, obtain a cycle leachate. Combine the primary leaching solution and all cycle leachates to obtain a mixed leachate. 4) Adjust the pH of the mixed leachate to 10-11, then add an alkaline solution for purification. After solid-liquid separation, a purified solution is obtained. 5) Carbon dioxide is introduced into the purified liquid to carry out a carbonization reaction. After filtration, washing, and drying, calcium carbonate is obtained.

2. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 1), the temperature of the digestion reaction is 40-60℃ and the time is 30-50 min; the liquid-solid ratio of the pretreated magnesium slag to deionized water is (15-25):

1.

3. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 1), the pretreatment steps for magnesium slag are as follows: dry the magnesium slag at 105-120℃ for 6-12 h, grind it and pass it through a 150-mesh sieve.

4. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In steps 2) and 3), the conditions for the ammonium leaching reaction are: an addition concentration of 1.5-2.5 mol·L⁻¹ -1 The reaction temperature of ammonium chloride is 40-60℃, and the reaction time is 30-50 min.

5. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 3), the number of times the cyclic ammonium leaching reaction is performed is one, that is, the leaching residue is subjected to one cyclic ammonium leaching to obtain a secondary leachate.

6. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 4), ammonia is added to adjust the pH of the mixed leachate to 10-11.

7. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 4), the alkaline solution is a sodium hydroxide solution, and the purification conditions are: an addition concentration of 0.5-1.5 mol·L⁻¹ -1 After adding sodium hydroxide solution, let it stand for 10-15 minutes.

8. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 5), the carbonization reaction temperature is 30-60℃, the carbonization reaction time is 9-12 min, and the carbon dioxide flow rate is 100-300 mL / min. -1 .

9. The method for preparing calcium carbonate using recycled ammonium leaching of magnesium slag according to claim 1, characterized in that, In step 5), the drying temperature is 105-120℃.

10. A calcium carbonate, characterized in that, The calcium carbonate is prepared by the method of ammonium leaching of magnesium slag according to any one of claims 1-9, wherein the mass fraction of calcium carbonate is ≥98.5% and the mass fraction of MgO is ≤0.03%.

Citation Information

Patent Citations

  • A high-efficiency and low-consumption leaching method for smelting slag based on ammonium salt leaching agent circulation

    CN120099291B

  • Light calcium carbonate and molecular sieve prepared by synergistically utilizing magnesium smelting byproducts and preparation method of light calcium carbonate and molecular sieve

    CN120328599A